2013
DOI: 10.1103/physreva.88.022510
|View full text |Cite
|
Sign up to set email alerts
|

Complete double valence photoionization study of the electron spectra of krypton

Abstract: This is the published version of a paper published in Physical Review A. Atomic, Molecular, and Optical Physics. Citation for the original published paper (version of record):Linusson, P., Hedin, L., Eland, J H., Squibb, R J., Mucke, M. et al. (2013) Complete double valence photoionization study of the electron spectra of krypton. Physical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Figure 2 shows the 4p −2 nl satellite lines of Kr excited by 99.00 eV (E exc =5.21 eV) photons in the binding energy region of 38.3-40.3 eV. The Kr + 4p −2 ( 1 D 2 )nd( 2 S) correlation satellites dominate the spectrum at 0°as shown with red dotted lines due to the strong configuration interaction between the 4 s −1 ( 2 S) and the 4p −2 nd( 2 S) [31][32][33][34][35][36][37]. The Kr + 4p −2 ( 1 D 2 )nd( 2 S) does not appear in the measurement of 90°thick blue lines in accord with a p-wave distribution of the ejected electron.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows the 4p −2 nl satellite lines of Kr excited by 99.00 eV (E exc =5.21 eV) photons in the binding energy region of 38.3-40.3 eV. The Kr + 4p −2 ( 1 D 2 )nd( 2 S) correlation satellites dominate the spectrum at 0°as shown with red dotted lines due to the strong configuration interaction between the 4 s −1 ( 2 S) and the 4p −2 nd( 2 S) [31][32][33][34][35][36][37]. The Kr + 4p −2 ( 1 D 2 )nd( 2 S) does not appear in the measurement of 90°thick blue lines in accord with a p-wave distribution of the ejected electron.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of the high collection e ciency of a magnetic bottle spectrometer and tunable synchrotron radiation, serves well for coincidences studies on Auger cascades. A few multi-electron coincidence studies on di erent noble gases [47][48][49][50][51] and a few examples on metal atoms [52][53][54][55], based on similar techniques existed prior to this thesis. These previous studies demonstrated the e ciency of the technique and the amount of information that can be obtained on electronic relaxation.…”
Section: Triple Ionization Of Metal Atomsmentioning
confidence: 99%
“…Double photoionization electron coincidence spectroscopy based on a magnetic bottle introduced by Eland et al 10 in 2003 opened up the possibility to determine the correlation of electrons with a wide range of kinetic energies. To begin with, this method was used to study valence double ionization of atoms and molecules [10][11][12][13][14][15][16][17][18][19] using a pulsed He lamp, and was subsequently applied to studies of core-valence double photoionization of atoms and molecules [20][21][22][23][24][25][26] utilizing synchrotron radiation sources. Both processes are examples of double ionization, where the two electrons emitted may share the excess energy provided by the absorbed photon arbitrarily, in contrast to fixed electron kinetic energies typically observed in cases of single core shell ionization followed by normal Auger decay.…”
Section: Introductionmentioning
confidence: 99%